INTEGRASI NILAI-NILAI PENTAKOSTA DALAM PEMBELAJARAN PENDIDIKAN AGAMA KRISTEN UNTUK MEMBENTUK SISWA YANG BERMISI DI ERA MODERN - Gulo, Moralman; Silaban, Elfrida Elena Br; Evimalinda, Rita (The Way: Jurnal Teologi dan Kependidikan, 2025)
Pentecost is an important event in the Christian faith that marks the outpouring of the Holy Spirit and the sending of believers to be on mission. In the context of Christian Religious Education (PAK) in the modern era, Pentecostal values ​​need to be integrated so that students not only understand Christian teachings theoretically but also have a missionary spirit in their overall growth process. The purpose of this study is to explore the strategy of integrating the meaning of Pentecost in Christian Religious Education learning in order to shape the character of students who are active in mission. The method used is a qualitative research method with a literature study approach and interviews with Christian students in high schools. Data were analyzed descriptively to understand the application of Pentecostal values ​​in Christian Religious Education learning. The results of the study indicate that the integration of the meaning of Pentecost in Christian Religious Education learning can be done through an experience-based approach, where teachers act as facilitators for students to live their faith through testimony, teaching the Word, participating in social action, church service and creatively utilizing social media as a platform for preaching the gospel. Thus, this study concludes that Christian Religious Education that integrates the meaning of Pentecost not only improves theological understanding but also forms the who are enthusiastic in realizing the mission of the Great Commission in realistic and effective ways. This finding contributes to the development of a more applicable and contextual Christian Religious Education curriculum.